1988
DOI: 10.1111/j.1749-6632.1988.tb21618.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Immunoglobulin Genes in Transgenic Mice and Transfected Cellsa

Abstract: Immunoglobulin (Ig) genes are expressed sequentially (first H-, then L-chain genes) during the development of B lymphocytes. These studies, performed with transgenic mice and transfected cells, were aimed at the regulation of turning on and off the rearrangement of Ig genes. The specific recombinase is active in pre-B cells, but not in plasma cells. Production of membrane mu, but not secreted mu or gamma-2b, turns off rearrangement of H genes. Feedback inhibition of kappa-gene rearrangement requires kappa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…There are few data relevant to allelic exclusion in y heavy chain transgenic mice. A lack of allelic exclusion has been reported in mice transgenic for a yl transgene (32) and generally in mice transgenic for a y2b transgene (33 (1992) the simultaneous production of protective and pathogenic antibodies may underlie the need for allelic exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…There are few data relevant to allelic exclusion in y heavy chain transgenic mice. A lack of allelic exclusion has been reported in mice transgenic for a yl transgene (32) and generally in mice transgenic for a y2b transgene (33 (1992) the simultaneous production of protective and pathogenic antibodies may underlie the need for allelic exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Storb and coworkers (Ritchie et al 1984, Gollahon et al 1988, Hagman et al 1989 find it necessary to treat each of their findings with different light chain transgenics as independent, unrelated phenomena; each observation is interpreted by a unique mechanism. They characterize two types of transgenic, one K (Ritchie et al 1984, Gollahon et al 1988, the other Xj (Hagman et al 1989). Hybridomas from the K-transgenic (TGK) were analyzed for the rearrangement of endogenous (E) IgK (Ritchie et al 1984) and for the expression of both K and X (TGA:-|-E^.)…”
Section: Assays On H~'~ Hybridomasmentioning
confidence: 96%
“…The only expected difTerences between given L-chain transgenics is quantitative and determined by the probability, on average, that complementation with an H-chain will effect the (LH)2-ST0P. In contrast, Storb and coworkers (Ritchie et al 1984, Gollahon et al 1988, Hagman et al 1989 find it necessary to treat each of their findings with different light chain transgenics as independent, unrelated phenomena; each observation is interpreted by a unique mechanism. They characterize two types of transgenic, one K (Ritchie et al 1984, Gollahon et al 1988, the other Xj (Hagman et al 1989).…”
Section: Assays On H~'~ Hybridomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas this rule seems to be quite effective in the case of the HC (4,5), it suffers remarkable exceptions at light chain (LC) loci. Indeed, several studies reported the presence of double-expressing ͞ B cells either at very low frequencies in normal mice or in human, and more abundantly in transgenic mice (6)(7)(8)(9) and plasmocytomas (10). Little is known about the mechanisms involved in the allelic exclusion of LC even if recent studies highlighted the importance of asymmetric demethylation of the locus (11,12) and feedback inhibition of the recombination machinery after the assembly and signaling by a non-self-reactive BCR (13)(14)(15)(16).…”
mentioning
confidence: 99%